2020
DOI: 10.5089/9781513554501.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Income Inequality and Implications for Economic Transmission Channels

Abstract: We study the channels that theoretically transmit the effects of inequality to economic growth, unlike much of the existing literature that focuses on the direct linkage. The role of inequality in these transmission channels is difficult to pin down and varies with the particular inequality indicator chosen. We run our analyses with six methodologically distinct inequality measures (Gini coefficients and Top10 income shares). Methodological differences within the set of Gini coefficients and the Top10 income s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Considering six different measures of inequality (three Gini coefficients and three top 10 income shares), a recent study by Blotevogel et al (2020) showed that the choice of the inequality indicator has important implications for the results obtained in empirical analysis, namely, when considering different transmission channels between inequality and growth. In the case of the link between inequality and governance, there is a concern that frequently used measures do not capture interclass inequality, which precludes the testing of the theoretical hypothesis on the effects on democracy that refer to inequality between classes (Houle 2015).…”
Section: Concept and Measurement Of Inequalitymentioning
confidence: 99%
“…Considering six different measures of inequality (three Gini coefficients and three top 10 income shares), a recent study by Blotevogel et al (2020) showed that the choice of the inequality indicator has important implications for the results obtained in empirical analysis, namely, when considering different transmission channels between inequality and growth. In the case of the link between inequality and governance, there is a concern that frequently used measures do not capture interclass inequality, which precludes the testing of the theoretical hypothesis on the effects on democracy that refer to inequality between classes (Houle 2015).…”
Section: Concept and Measurement Of Inequalitymentioning
confidence: 99%
“…The negative channels are related to imperfect capital markets (Banerjee and Newman, 1993;Galor and Zeira, 1993), political economy issues (Alesina and Rodrik, 1994;Stiglitz, 2012), and the development process (Dasgupta and Ray, 1986). An additional complication is that estimated channels may change over time (Blotevogel et al, 2020). 2 In the literature on inequality of opportunity, a similar hypothesis (in terms of inequality of opportunity and inequality of effort) has been named the "cholesterol hypothesis" (Ferreira, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Compounding these issues, data on poverty and inequality have been difficult to compile, are collected and measured infrequently, and are often unreliable. Estimates are sensitive to assumptions on factors such as capital gains and untaxed income (Cerra et al 2021, Chapter 1) and alternative measures may show different trends (Blotevogel et al 2020). Empirical studies, especially those exploring the link between growth and inequality, sometimes find inconsistent results, no doubt due to these multiple channels, endogenous relationships, and poor data quality.…”
Section: Introductionmentioning
confidence: 99%